PENGARUH PROFITABILITAS, LEVERAGE, SALES GROWTH DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE - Laihah, Lala Atul; Widyasari, Widyasari (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study is to identify the effect of Profitability, Leverage, Sales growth and Capital intensity on Tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2020 period. The technique in this study used a nonprobability sampling approach with purposive sampling technique aimed at obtaining samples in study using 17 manufacturing companies as research samples. The results contained in this study conclude that there is a significant influence between the independent variables, namely Profitability, Leverage, and Capital intensity on Tax avoidance. While the independent variable Sales growth there is no significant effect on Tax avoidance.